MicroRNA dysregulation in rhabdomyosarcoma: a new player enters the game. (23rd July 2015) - Li, Zheng; Yu, Xin; Shen, Jianxiong; Liu, Yang; Chan, Matthew T. V.; Wu, William K. K.
Abstract Rhabdomyosarcoma (RMS) is the most common of the soft tissue sarcomas with resultant high morbidity, frequently occuring in paediatric patients and young adults. While the molecular basis of RMS has received considerable attention, exact mechanisms underlying its development and metastasis remain unclear. MicroRNAs (miRNAs) are endogenously expressed small non‐coding RNAs that negatively regulate gene expression via translational inhibition or mRNA degradation. Deregulated expression of miRNA has been implicated in initiation, progression, and metastasis of RMS. miRNAs have emerged as key regulators of several physiological and pathophysiological processes and have opened new avenues for diagnosis and treatment of RMS. This review summarizes deregulation and functional roles of miRNAs in RMS and their potential applications for diagnosis, prognosis and treatment of this malignancy. As a rapidly evolving field in basic and translational medicine, it is hopeful that miRNA research will ultimately improve management of RMS.